4(x+9)+3=4x+7

Simple and best practice solution for 4(x+9)+3=4x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+9)+3=4x+7 equation:


Simplifying
4(x + 9) + 3 = 4x + 7

Reorder the terms:
4(9 + x) + 3 = 4x + 7
(9 * 4 + x * 4) + 3 = 4x + 7
(36 + 4x) + 3 = 4x + 7

Reorder the terms:
36 + 3 + 4x = 4x + 7

Combine like terms: 36 + 3 = 39
39 + 4x = 4x + 7

Reorder the terms:
39 + 4x = 7 + 4x

Add '-4x' to each side of the equation.
39 + 4x + -4x = 7 + 4x + -4x

Combine like terms: 4x + -4x = 0
39 + 0 = 7 + 4x + -4x
39 = 7 + 4x + -4x

Combine like terms: 4x + -4x = 0
39 = 7 + 0
39 = 7

Solving
39 = 7

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| f(2.75)=x+1 | | -34-4x=23-x | | -0.7-0.6=-0.2y+3.4 | | 10x+20+20y= | | x-12y=-158-x | | 8a-(2+5)=2(a-1) | | 7x-3=5x+5x | | 0.20(y-5)+0.10y=0.18y-0.7 | | 6m=4m+17 | | 1.5x-2-3.5x=18 | | 3x+2yb=7 | | 7x+6-3x=-6x-14+x | | 2q-38=3q-86 | | 5x-27=3x+411 | | (b+2)9= | | 0.12y(y-6)+0.04y=0.08y-0.7 | | -4x-15-3x=-64 | | 13-(x+6)=6x-7 | | 5-2(x-1)-2=12 | | 7(3x+1)-(x+5)=-52 | | 9-6x=-15x | | (3x-12)=51 | | -3+2n=-2 | | 0=-8x^10+32x^9-48x^8+32x^7-8x^6 | | 0.5x^5-0.3x= | | (8+x)*m=5m | | 3X-12Y=-1 | | -5(y+7)=5 | | -10=-x+2-2x | | X+7=3x-21 | | 4+-2y=-11+3y | | 12x-3=32x+2 |

Equations solver categories